Society for the Advancement of Transplant Anesthesia: Liver Transplant Anesthesia Fellowship—White Paper Advocating Measurable Proficiency in Transplant Specialties Training. (December 2017) - Chadha, Ryan M.; Crouch, Cara; Zerillo, Jeron; Pretto, Ernesto A.; Planinsic, Raymond; Kim, Sang; Nicolau-Raducu, Ramona; Adelmann, Dieter; Elia, Elia; Wray, Christopher L.; Srinivas, Coimbatore; Mandell, M. Susan
The anesthesia community has openly debated if the care of transplant patients was generalist or specialist care ever since the publication of an opinion paper in 1999 recommended subspecialty training in the field of liver transplantation anesthesia. In the past decade, liver transplant anesthesia has become more complex with a sicker patient population and evolving evidence-based practices. Transplant training is currently not required for accreditation or certification in anesthesiology, and not all anesthesia residency programs are associated with transplant centers. Yet there is evidence that patient outcome is affected by the experience of the anesthesiologist with liver transplants as part of a multidisciplinary care team. Requests for a formal review of the inequities in training opportunities and requirements led the Society for the Advancement for Transplant Anesthesia (SATA) to begin the task of developing post-graduate fellowship training recommendations. In this article, members of the SATA Working Group on Transplant Anesthesia Education present their reasoning for specialized education and conclusions about which pathways can better prepare trainees to care for complex transplant patients.